Large-scale Networked Multi-axis Control solution using EtherCAT and Soft Logic - Zhiyuan Cheng; Qing Ma; Minqi Yan; Yu Zhang (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Aiming at the deficiencies of the traditional multi-axis control solution such as complex networked structure, poor clustered-control feature and unsatisfactory engineering practicability, the paper firstly optimized the existing solution in networked fieldbus, controller model, engineering reliability and maintainability. Then it proposed a novel solution combined high speed real-time EtherCAT (Ethernet for control Automation Technology) fieldbus with soft logic controller. The new solution took advantage of extraordinary real-time performance of EtherCAT and made good use of powerful clustered-control architecture of soft logic controller. Thus the new solution is concise and effective to solve the Large-scale networked controlling problem of 1100 distributed motors. Compared with the traditional schemes, the engineering practice shows that the novel solution has the advantage of perfect real-time performance, powerful clustered-control capability, flexible and variable networked structure, excellent engineering practicability.The novel solution is worth using for reference in solve similar large-scale networked controlling problems. DOI: http://dx.doi.org/10.11591/telkomnika.v11i9.3271